HAK ASASI MANUSIA DI DUNIA ISLAM - Achmad Saeful; Imam Turmidzi (Institut Binamadani Indonesia, 2023)
This article is about human rights in the Islamic world. This study confirms that human rights are an important part of Islamic teachings. Since the beginning of its arrival Islam has greatly accommodated the concept of human rights. Nevertheless, the concept of human rights at the beginning of its emergence, precisely in the Declaration of Human Rights of December 10, 1948 was not approved by some Islamic countries, considered a product of the West and not part of Islam. On the other hand, in the practice of its application, Muslim countries in Southeast Asia, such as Indonesia, Malaysia and Brunei Darussalam are very different, but these countries at least agree on one word, that the concept of human rights should be upheld and actualized in the life of the nation and state.